Hematological and hormonal changes in elite female swimmers - VanHeest, J. L.; Ratliff, K. (Medicine & Science in Sports & Exercise, 1998)
International and national caliber female swimmers (N = 12) were evaluated over a 16-week period for blood and hormonal parameters. The total group and two sub-groups, based on peak-performance data, were analyzed. Swimmers who improved by more than 3% over the period were deemed to have "improved" while the others were classified as "non-improved." Assessments occurred in the first week, week 8 (mid-season), and week 16 (taper). The hypothesis tested was: relationships seen with sub-elite athletes would persist and become stronger in elite swimmers as a result of the type of training performed. No significant changes were observed in ferritin, hematocrit, red blood cell count, white blood cell count, % monocytes, % lymphocytes, % eosinophils, platelets, cortisol, testosterone, and testosterone:cortisol ratio for the total group. Iron and hemoglobin tended to decrease while % basophils increased over time. Differences between improvers and non-improvers were evident at the start of the investigation in testosterone and T:C ratio. Non-improvers changed over the 16 weeks in cortisol, lymphocytes, and neutrophils. These elite swimmers responded differently to previously reported work with sub-elite athletes. Blood and hormonal factors were not clear indicators of training responses and should only be contemplated when used with other factors associated with training. Implication. Blood and hormonal factors do not indicate training responses in elite female swimmers.